Photonic, electronic and atomic collisions :proceedings of the XXIV International Conference, Rosario, Argentina, 20-26 July 2005 /editors, Pablo D. Fainstein ... [et al.]. - Lima, Marco Aurelio P.editors
Includes bibliographical references and name index.